Child welfare inequalities in the four nations of the UK. (March 2020) - Bywaters, Paul; Scourfield, Jonathan; Jones, Chantel; Sparks, Tim; Elliott, Martin; Hooper, Jade; McCartan, Claire; Shapira, Marina; Bunting, Lisa; Daniel, Brigid
Comparative international data on patterns of inequality in child welfare interventions, for example, the proportion of children about whom there are substantiated child protection concerns or who are in out-of-home care, are far less developed than data about inequalities in health. Few countries collect reliable, comprehensive information and definitions, methods of data collection and analysis are rarely consistent. The four UK countries (England, Northern Ireland, Scotland and Wales) provide a potential 'natural experiment' for comparing intervention patterns. This study reports on a large quantitative, descriptive study focusing on children in contact with children's services on a single date in 2015. It found that children's chances of receiving a child protection intervention were related to family socio-economic circumstances, measured by neighbourhood deprivation, within all four countries. There was a strong social gradient which was significantly steeper in some countries than others. Ethnicity was another important factor underlying inequalities. While inequalities in patterns of intervention between the four countries were considerable, they did not mirror relative levels of deprivation in the child population. Inequalities in intervention rates result from a combination of demand and supply factors. The level and extent of inequity raise profound ethical, economic and practical challenges to those involved in child protection, the wider society and the state.